Screening method for the detection of residues of amphenicol antibiotics in bovine milk by optical biosensor. Issue 11 (1st November 2020) - Thompson, Colin S.; Traynor, Imelda M.; Fodey, Terence L.; Barnes, P.; Faulkner, Dermot V.; Crooks, Steven R.H.
ABSTRACT: An immunobiosensor assay was developed for multi-residue screening in bovine milk of the parent amphenicols, thiamphenicol and florfenicol, along with the metabolite florfenicol amine. A polyclonal antibody raised in a rabbit after immunisation with a florfenicol amine-protein conjugate was employed in the assay. Milk samples were subjected to acetonitrile extraction, reconstituted in buffer and diluted prior to biosensor analysis. Validation data obtained from the analysis of fortified samples has shown that the method has a detection capability of less than 0.25 µg kg −1 for florfenicol and less than 0.5 µg kg −1 for florfenicol amine and thiamphenicol. The cross-reactivity profile and validation data for the detection of these amphenicols is presented together with results obtained following the analysis of florfenicol incurred samples using the developed screening method along with a comparison of results obtained from the analysis of the same incurred samples using an MRM 3 UPLC-MS/MS confirmatory method. Results are also presented obtained from the analysis of samples from both treated and non-treated animals which were co-housed and which show the potential for cross-contamination. Graphical Abstract: uf0001